Integrated microfluidic systems with sample preparation and nucleic acid amplification. Issue 17 (31st July 2019) - Yin, Juxin; Suo, Yuanjie; Zou, Zheyu; Sun, Jingjing; Zhang, Shan; Wang, Beng; Xu, Yawei; Darland, Diane; Zhao, Julia Xiaojun; Mu, Ying
Abstract : Integrated microfluidic systems with sample preparation and nucleic acid amplification can increase treatment efficiency and improve care. Abstract : Rapid, efficient and accurate nucleic acid molecule detection is important in the screening of diseases and pathogens, yet remains a limiting factor at point of care (POC) treatment. Microfluidic systems are characterized by fast, integrated, miniaturized features which provide an effective platform for qualitative and quantitative detection of nucleic acid molecules. The nucleic acid detection process mainly includes sample preparation and target molecule amplification. Given the advancements in theoretical research and technological innovations to date, nucleic acid extraction and amplification integrated with microfluidic systems has advanced rapidly. The primary goal of this review is to outline current approaches used for nucleic acid detection in the context of microfluidic systems. The secondary goal is to identify new approaches that will help shape future trends at the intersection of nucleic acid detection and microfluidics, particularly with regard to increasing disease and pathogen detection for improved diagnosis and treatment.